ANTIBACTERIAL ACTIVITY TEST OF COMBINATION OF BETEL LEAF EXTRACT (PIPER BETLE) AND KERSEN LEAF EXTRACT (MUNTINGIA CALABURA) AGAINST ESCHERICHIA COLI BACTERIA - T, Ardy Tanfil; Hermawati, Ema; Subagiyo, Ahmad (Fakultas Farmasi, Universitas Muslim Indonesia, 2022)
Escherichia coli or commonly referred to as E. coli is a Gram-negative bacteria that can cause various problems in the human body, the mechanism of resistance built by E.Coli to antibiotics is a reason for the need to look for compounds that have antibacterial potential. Betel leaf and cherry leaf are two types of plants that have the potential to have compounds that can be developed as antibacterial, this study tested the two types of plants using the disc diffusion method. The compounds identified in this plant are alkaloids, saponins, and flavonoids. These three compounds are thought to provide strong antibacterial activity in the samples, although further research is still needed to confirm this.